Specificity of Formation of Linguistic Competence of Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The study identifies the specifics of the formation of linguistic competence among students, determined by the following main parameters: heterogeneity of the first-year student cohort in terms of speech preparation; the particularities of the joint activity of the teacher and the student in the process of subject-based learning of the disciplines "Russian Language" and "Culture of Speech"; the acute shortage of study time for the disciplines "Russian Language" and "Culture of Speech" according to the curriculum; the necessity of skillfully combining all types of productive speech activities (speaking, writing, reading, listening); the influence of the national-ethnic factor on the communicative-speech interaction of students.